SENSITIVITY AND SPECIFICITY OF ULTRASONOGRAPHY IN CASES OF SUSPECTED ACUTE APPENDICITIS; RESULTS OF A CROSS-SECTIONAL SURVEY - Ihsan, Hussain Rashid; Ayaz, Saeed Bin; Farooq, Muhammad; Saeed, Muhammad; Aslam, Sohail (Pakistan Armed Forces Medical Journal, 2017)
Objective: To evaluate the accuracy of ultrasonography in the diagnosis of acute appendicitis. Study Design: A cross-sectional validation study. Place and Duration of Study: Department of radiology, Sheikh Khalifa Bin Zaid Al Nahyan Hospital Muzaffarabad, Azad Jammu and Kashmir, from Oct 2015 to Apr 2016. Material and Methods: Patients, >18 years of age, who were clinically suspected to have acute appendicitis and scored 5 or higher on Modified Alvarado Scoring System were included through consecutive sampling. All participants underwent ultrasonographic examination while using graded-compression technique. The sonographically positive patients for acute appendicitis underwent surgery and the removed appendix was examined for the signs of inflammation. The sonographically negative patients for acute appendicitis were kept on conservative management. They were operated later if they did not show improvement with conservative management and their appendix was re-examined for signs of inflammation. Results: Out of 100 patients, 64 were male and 36 were female (mean age: 30 ± 7 years). Ultrasonographic evaluation was positive in 72 patients and negative in 28 patients. Sixty-four sonographically positive patients had positive operative findings while 12 out of 28 sonographically negative patients for acute appendicitis had to be operated because they did not show improvement with conservative management. The sensitivity of ultrasonography was 84%, while specificity was 67% with positive predictive value of 89%, negative predictive value of 57%, and accuracy rate of 80%. Conclusion: Ultrasonography, with a diagnostic accuracy of 80% was found effective in the diagnosis of acute appendicitis, and recommended as a screening tool in suspected cases of acute appendicitis.